2008
DOI: 10.2337/dc07-1338
|View full text |Cite
|
Sign up to set email alerts
|

Salsalate Improves Glycemia and Inflammatory Parameters in Obese Young Adults

Abstract: OBJECTIVE -Sedentary lifestyle and a western diet promote subacute-chronic inflammation, obesity, and subsequently dysglycemia. The aim of the current study was to evaluate the efficacy of the anti-inflammatory drug salsalate to improve glycemia by reducing systemic inflammation in obese adults at risk for the development of type 2 diabetes.RESEARCH DESIGN AND METHODS -In a double-masked, placebo controlled trial, we evaluated 20 obese nondiabetic adults at baseline and after 1 month of salsalate or placebo.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
227
2
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(244 citation statements)
references
References 36 publications
13
227
2
2
Order By: Relevance
“…This proof-ofprinciple study demonstrates that salsalate reduces glycaemia and may improve inflammatory cardiovascular risk indexes in overweight individuals [32]. In addition, aspirin treatment improved glycaemic control of diabetic patients, in parallel with reductions in inflammatory response, including reduced levels of serum nitrite, which at least in part may be secondary to reduced iNOS activation [33].…”
Section: Discussionmentioning
confidence: 89%
“…This proof-ofprinciple study demonstrates that salsalate reduces glycaemia and may improve inflammatory cardiovascular risk indexes in overweight individuals [32]. In addition, aspirin treatment improved glycaemic control of diabetic patients, in parallel with reductions in inflammatory response, including reduced levels of serum nitrite, which at least in part may be secondary to reduced iNOS activation [33].…”
Section: Discussionmentioning
confidence: 89%
“…This suggested an inability to respond to challenge, akin to anergy or LPS tolerance, despite the fact that the Tg mice had never before been challenged with LPS. Given our interest in using the antiinflammatory drug salicylate to treat insulin resistant states related to inflammation (8,22,24,25), we also analyzed the ability of this drug to suppress LPS-induced cytokine gene expression. Mice were chronically treated with salicylate in their diet (4 g/kg), as we typically do to treat insulin resistance in obese C57BL/6J mice.…”
Section: Resultsmentioning
confidence: 99%
“…Two methods are available to conveniently target inflammation in obese mice as a way of improving insulin resistance. The first is the antiinflammatory drug salicylate, an effective pharmacologic inhibitor of NF-κB and insulin sensitizer in rodents and humans (8,(22)(23)(24)(25). The other uses Cre-Lox technology to genetically delete IκB kinase β (IKKβ) and thus inhibit NF-κB, in myeloid cells (Ikkβ Δmye ), including macrophages (26).…”
Section: Resultsmentioning
confidence: 99%
“…The first clinical trials with high dose (≥3 g) salsalate or the salicylate derivative trifusal indeed showed that fasting glucose levels decreased in nondiabetic, mostly obese, persons while insulin concentrations increased in the context of reduced insulin clearance [90][91][92]. In a pilot trial of 7 g aspirin/day for 2 weeks in nine patients with type 2 diabetes, similar changes were observed, with mean fasting plasma glucose levels falling from 9.1 to 6.9 mmol/l [93].…”
Section: Lessons From Immune Intervention Trialsmentioning
confidence: 99%